Penerapan Model Pembelajaran Inkuiri Terbimbing untuk Meningkatkan Kompetensi Siswa dalam Pembelajaran Biologi - Evi Suryawati Suryawati; Suwondo Suwondo; Pendrice Pendrice (Jurnal Pendidikan Biologi, 2018)
Application of Guided Inquiry Learning Model to Improve Student Competency in Biology Learning at SMAN 2 XIII Koto Kampar. The classroom action research was motivated by the low competence of students in aspects of attitudes, knowledge and skills. The purpose of this study was to determine improving student competence of grouping plant in class X IPA 2 SMAN 2 XIII Koto Kampar through the application of guided inquiry learning model. This research was conducted in two cycles, each cycle consisting of planning, implementation, observation and reflection. This study begins with a pre cycle before the cycle I. Subjects were 26 students of SMAN 2 X IPA 2 class XIII Koto Kampar. Data obtained using the competency attitude instrument observation sheet of religious and social attitudes, including: faithful, honest, discipline, cooperation, tolerance and mutual cooperation. A knowledge data was collected with quiz and test questions at the end of the cycle.  The skills data was collected with observation sheets of practices and product. The results showed an increase in the competence of the students after the applied application of guided inquiry learning model. An increase in the average value of attitude competence of the first cycle of 3.15 and the second cycle of 3.49. The competence of knowledge showed an increase from the first cycle of students who pass as many as 22 people (84.62%) in the second cycle students who pass as many as 24 people (92.31%), while competence of skills to practice skills in the first cycle of 3.16, and the second cycle of 3.30. And then, product skills in the first cycle of 3.04 increased in the second cycle of 3.30.Keywords: Grouping Plants, Guided Inquiry, Student Competence